PERKEMBANGAN PENGATURAN PELAKSANAAN PENGANGKATAN ANAK DI INDONESIA - Nurma Suspitawati Tambunan; Syawal Amry Siregar (JURNAL RETENTUM, 2020)
Abstarct The implementation of adoption of children has been known in Indonesian society for a long time, but regulations regarding the implementation of adoption have not been clearly regulated, so this creates legal uncertainty for prospective adopted children. Since Indonesia's independence in the year 1945, the adoption of children has not been regulated in a statutory regulation. Adoption of Children was only based on regulations made by the Dutch East Indies for ethnic Chinese in Indonesia, which was Stbl 1917 Number 129. Meanwhile for the Indonesian people themselves, it was based on customary and customary law, in accordance with their respective regions. Therefore it is considered necessary to get to know about the development of the implementation regarding to the adoption of children in Indonesia.